2021
DOI: 10.1590/2175-8239-jbn-2020-0236
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines production by kidney tissue and mesangial cell culture is differentially modulated by diabetes

Abstract: Introduction: According to the International Diabetes Federation, the number of people with diabetes mellitus may reach 700 million in 2045. Catecholamines are involved in the regulation of several kidney functions. This study investigates the effects of hyperglycemia on catecholamines' metabolism in kidney tissue from control, diabetic, and insulin-treated diabetic rats, both in vivo and in vitro. Methods: Male Wistar-Hannover rats were randomized into: control, diabetic, and insulin-treated diabetic groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Early studies demonstrated that isolated rat kidneys can synthesize epinephrine, norepinephrine, and dopamine ( 87 ). Renal tubular cells are able to produce large amounts of dopamine, whereas cultivated glomerular mesangial cells can synthesize epinephrine, norepinephrine and dopamine ( 88 ), all of which may exert a key role in the renal processing of sodium. The renal microcirculation is an obvious target of locally produced substances, especially catecholamines.…”
Section: Reappraisal Of the Physiological Role Of The Adrenergic Nerv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies demonstrated that isolated rat kidneys can synthesize epinephrine, norepinephrine, and dopamine ( 87 ). Renal tubular cells are able to produce large amounts of dopamine, whereas cultivated glomerular mesangial cells can synthesize epinephrine, norepinephrine and dopamine ( 88 ), all of which may exert a key role in the renal processing of sodium. The renal microcirculation is an obvious target of locally produced substances, especially catecholamines.…”
Section: Reappraisal Of the Physiological Role Of The Adrenergic Nerv...mentioning
confidence: 99%
“…The renal endothelium is well known to synthesize and release a wealth of vasoactive compounds, such as vasodilating and vasoconstrictor prostaglandins, endothelin, and sulfidric gas ( 89 ). Direct evidence that renal endothelial cells release catecholamines or express the enzymes involved in their biosynthesis is currently lacking, although this capability has been shown for mesangial cells that can synthesize epinephrine, norepinephrine, and dopamine ( 88 ). However, evidence that these compounds are synthesized and released by endothelial cells of other territories has been obtained in mice, bovine aorta, and human umbilical cord vessels ( 16 , 24 ), a finding compatible with the notion that the vascular endothelium can participate in the local regulation of the microcirculation.…”
Section: Reappraisal Of the Physiological Role Of The Adrenergic Nerv...mentioning
confidence: 99%